Validation of the Revised Quick Cognitive Screening Test - Mate-Kole, C.C.; Conway, J.; Catayong, K.; Sackey, N.; Bieu, R.; Fellows, R.; Wood, R. (My University, 2009)
In an effort to examine the reliability and validity of the RQCST, participants were administered the revised QCST with a number of standardized measures. The results revealed that the RQCST discriminated between healthy controls and the neuropsychiatric participants. Additionally, the RQCST significantly correlated with other standardized measures confirming the RQCST’s reliability and validity as a screening instrument for individuals with cognitive deficits. The RQCST provides the clinician with a short, yet reliable screening instrument in detecting cognitive deficits in individuals with dementia and other neurological conditions